OPTIMIZATION OF PUBLIC AND PRIVATE COMPONENT OF PENSION SECURITY: FOREIGN EXPERIENCE - KRUPA, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The increase in life expectancy and the significant decrease in the mortality rate of the middle-aged population, which has been observed in recent decades, has had a noticeable impact not only on the life plans and savings of individuals, but also on the economies of individual countries as a whole. The increase in the fiscal burden is one of the key macroeconomic effects of population aging, and this effect is one of the key incentives for reforming and improving existing pension systems. And although world practice has developed various approaches and practices the use of differentiated sources of retirement support for the elderly, the issue of the optimal combination of state and private components in the pension system requires further research. The purpose of the study consists in the study of the world’s leading experience in the organization of three-pillar pension systems, the characteristics of the each pillar key problems, opportunities and applied approaches to optimizing private and state components of pension security. In the article studied the level structure of an effective pension system according to World Bank conclusions. Considered the advantages and disadvantages of the each pillar practical implementation as well as the best global practices of their application. Carried out an analysis of the pensions level in Ukraine and the shortcomings of the draft law on the accumulative pension system. Proven the necessity of balancing the domestic pension system with a private component.